Discovery of Pyrano[2,3-c]pyrazole Derivatives as Novel Potential Human Coronavirus Inhibitors: Design, Synthesis, In Silico, In Vitro, and ADME Studies - Abdou K. Allayeh; Aliaa H. El-boghdady; Mohamed A. Said; Mahmoud G. A. Saleh; Mohammed T. Abdel-Aal; Mohamed G. Abouelenein (MDPI AG, 2024)
The SARS-CoV-2 pandemic at the end of 2019 had major worldwide health and economic consequences. Until effective vaccination approaches were created, the healthcare sectors endured a shortage of operative treatments that might prevent the infection's spread. As a result, academia and the pharmaceutical industry prioritized the development of SARS-CoV2 antiviral medication. Pyranopyrazoles have been shown to play a prominent function in pharmaceutical chemistry and drug sighting because of their significant bioactive properties. We provide herein a novel sequence of pyranopyrazoles and their annulated systems whose antiviral efficacy and cytotoxicity were explored versus human coronavirus 229E (HCoV-229E) Vero-E6 cell lines as a model for the Coronaviridae family. Fifteen synthetic congeners pointed out miscellaneous antiviral efficacies against HCoV-229E with variable inhibition degrees. Compound 18 showed a high selectivity index (SI = 12.6) that established spectacular inhibitory capacity against human coronavirus 229E. Compounds 6, 7, and 14 exposed moderate efficacies. Compounds 6, 7, 14, and 18 exhibited substantial antiviral action through the replication phase with reduction percentages extending from 53.6%, 60.7%, and 55% to 82.2%, correspondingly. Likewise, when assessed to the positive control tipranavir (88.6%), the inhibitory efficiency of compounds 6, 7, 14, and 18 versus the SARS-CoV2 Mpro provided high percentages of 80.4%, 73.1%, 81.4% and up to 84.5%, respectively. In silico studies were performed to investigate further the biological activity and the target compounds' physical and chemical features, including molecular dynamic (MD) simulations, protein-ligand docking, ADME studies, and density functional theory (DFT) calculations. These inquiries demonstrated that this series of metabolically stable pyranopyrazoles and their annulated systems are effective human coronavirus inhibitors that inhibit the viral Mpro protein and may have emerged as a novel COVID-19 curative option.